Development and Factorial Validation of Meta-Cognitive Awareness Inventory in Physics (MAIP) for Senior Secondary School Students in Benue State, Nigeria - Barnabas Obiaje Ellah; Sunday Oche Emaikwu; Amalonye Dayalata Ethel Obinne; Odihi Adikwu (EDUPEDIA PUBLISHER, 2023)
Purpose: The study developed and factorial validated of Meta-cognitive Awareness Inventory in Physics (MAIP) for senior secondary school students in Benue State, Nigeria. Three research questions and one null hypothesis guided the study. Methodology: The study adopted instrumentation design. The sample comprised 1382 SSII students that offered Physics as a school subject for 2020/2021 Academic Session. The Meta-cognitive Awareness Inventory in Physics (MAIP) was face validated by five experts. Construct validation was carried out on the instrument. Coefficient of internal consistency was obtained through Cronbach’s Alpha and found to be 0.78. The research questions were answered using factor analysis, coefficient of internal consistency, mean and standard deviations. The null hypothesis was tested using independent t-test at 0.05 level of significance. Findings: The findings revealed that MAIP has 52 factorially simple or pure items and 23 factorially complex items in terms of their factor loadings. The coefficient of internal consistency of MAIP was found to be 0.98. It was also found that there was statistically significant difference in the mean meta-cognitive awareness ratings of students in rural and urban areas in favour of students in urban area using MAIP. Signifinance: It was recommended among others that Senior Secondary students should use the MAIP to determine their level of meta-cognitive awareness in Physics in both urban and rural schools. This may enable them to gain awareness and control over themselves as learners for effective learning of Physics in secondary schools irrespective of their locations.